Novi horizonti primene metotreksata - Maksimovic, Vladimir; Golocorbin-Kon, Svetlana; Mikov, Momir; Cvejic, Jelena; Pavlovic Popovic, Zora; Vukmirovic, Sasa (PONS - medicinski časopis, 2020)
Methotrexate is an anti-inflammatory and anticancer drug that has been used in the treatment of various oncological and inflammatory diseases (such as rheumatoid arthritis, inflammatory bowel disease, psoriasis, sarcoidosis, etc.). Scientists are working on finding optimal formulation that will maintain its efficacy and improve safety and nanoparticles have shown to be carriers with great potential as they protect the drug from degradation while at the same time they increase absorption. In vivo and in vitro studies of numerous nanoparticle preparations have showed that they generally have appropriate characteristics and can be carriers for targeted delivery of methotrexate to the tissues affected by disease. Topical preparations of methotrexate, mainly for the treatment of psoriasis, have also been assessed in various research and have showed promising results. Further research is warranted by the obtained results and will hopefully lead to new methotrexate formulations that will be approved by regulatory authorities and used instead of existing ones to improve efficacy of the drug and patients’ safety.